2017
DOI: 10.1002/bmc.3998
|View full text |Cite
|
Sign up to set email alerts
|

A simple and sensitive high‐performance liquid chromatography–electrochemical detection assay for the quantitative determination of monoamines and respective metabolites in six discrete brain regions of mice

Abstract: A rapid, sensitive, and reproducible assay is described for the quantitative determination of the monoamine neurotransmitters dopamine, norepinephrine and serotonin, their metabolites, and the internal standard 3,4-dihydroxybenzlyamine hydro-bromide in mouse brain homogenate using high-performance liquid chromatography with electrochemical detection. The method was validated in the following brain areas: frontal cortex, striatum, nucleus accumbens, hippocampus, substantia nigra pars compacta and ventral tegmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…Deviations in biological samples were <15% for all analytes and generally <10%, as suggested by the US Food and Drug Administration's requirements for bioanalytical method validation (Table ). These values are also in accordance with Zhang et al () and Allen et al (). The only exception to this is MHPG.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Deviations in biological samples were <15% for all analytes and generally <10%, as suggested by the US Food and Drug Administration's requirements for bioanalytical method validation (Table ). These values are also in accordance with Zhang et al () and Allen et al (). The only exception to this is MHPG.…”
Section: Resultssupporting
confidence: 93%
“…The LOD ranged from 0.625 to 2.5 pg/μL, while the LOQ was between 2.5 and 5 pg/μL (Table ). These values are in the same range or lower than those Zhang et al () achieved with a boron‐doped electrode, but four to five fold higher than the ones found by Allen et al ().…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…This indicated that the urethane-anesthetized mice used in this study might not be exposed to excess nervous stress or promotion of the brain nervous system. 21,22 The amounts of DA, NE, and HVA detected in the brain samples from the three mice using the aforementioned LC-TOF/MS procedures ranged from 21.6 to 29.0, 9.0 to 9.2, and 4.3 to 5.7 pmol/mg, respectively ( Table 2), and were comparable to the reported levels of DA, NE, and HVA (in pmol) in brain tissue samples. 22 As shown in Fig.…”
Section: Detection Of Endogenous Catecholamine Metabolites In Mouse Bsupporting
confidence: 69%